WHAT IS RESEARCHED IN NURSING - Fátima Luna Pinheiro Landim; Consuelo Helena Aires de Freitas Lopes; Maria Nazaré de Oliveira Fraga; Marta Maria Coelho Damasceno (Universidade Federal do Paraná, 2001)
The objective of this research was to analyze dissertations produced in the Program of Masters degree in nursing of UFC, intending to evidence relationships between intellectual production and health priorities of the population of Fortaleza. The study is about a bibliographical research over 48 defended dissertations in the period of 1993 until March, 1999. As a result of the study, it was verified that, unlike the enormous dynamics that the decisive phenomena of the process of health-disease was shown in the city of Fortaleza - following a reality dictated by the variable weather, the seasons and epidemics, as well as social-economics factor and others related with the heredity - the master's degree dissertations, elaborated and defended in the considered interval of time, maintained the same approach profile, which was characterized by the great variety of developed themes, without, necessarily, represent as main focus of interest, morbid processes that define the real status of the local epidemic.